EVALUASI WAKTU TUNGGU PELAYANAN RESEP DI RUMAH SAKIT X - fiman, imran; Marwan, Aulia (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Prescription service waiting time is one indicator of the quality of pharmaceutical services in hospitals, where excessive wait times can impact patient satisfaction with the service. Based on Regulation of the Minister of Health of the Republic of Indonesia Number 129/Menkes/SK/II/2008, the maximum standard wait time for non-compounded prescriptions is ≤ 30 minutes and for compounded prescriptions is ≤ 60 minutes. This study aims to evaluate the waiting time for prescription services in the Outpatient Pharmacy Unit of X Hospital. This study used a descriptive analytical method with a non-experimental quantitative approach. Data were collected prospectively through direct observation of prescription services using a purposive sampling technique and analyzed using Microsoft Excel. The results showed that the average wait time for non-compounded prescriptions was 51 minutes and for compounded prescriptions 82.2 minutes. Both categories fall short of the Ministry of Health's prescription service waiting time standards, which are ≤ 60 minutes for compounded and ≤ 30 minutes for non-compounded. Factors influencing waiting times for services include medication availability, the number and completeness of prescriptions, and the adequacy and skills of the pharmacy staff. Therefore, waiting times for prescription services at X Hospital do not meet minimum service standards, necessitating improvements in the efficiency of the pharmaceutical service system.